Early Warning System Means and Tools in the African Union and the Organization of American States: An Analytical Study - Lahmood, Firas Ammar; Mutlak, Donia Jawad (Journal of Ecohumanism, 2024)
Disasters, crises and wars are a serious and unforeseen threat. The capacity of the early warning system to monitor such crises is therefore crucial. The ability to make quick decisions in a short time is necessary to prevent crises from occurring. Here, the role and effectiveness of the early warning system emerges through its ability to monitor, record and analyze signals. It can also be evidenced by its ability to immediately convey these indicators to the concerned authorities to take measures that ensure these conflicts and disasters do not worsen. The system’s ability to detect disasters and crises, identify the crisis and its type, and use the scientific method and common sense to deal with it is something that contributes to finding the best way to manage the crisis. Thus, the adverse effects of crises can be avoided, including: physical and moral effects, effects with a clear direct impact of the crisis, or indirect effects, long-term, medium-term and short-term effects. Therefore, in this study, we will try to demonstrate the means and tools of early warning systems in the African Union in a way that allows us to identify the most prominent benefits and disadvantages of these systems, and then analyze them in detail.